A microwave‐based one‐pot process for homogeneous surface coating: improved electrochemical performance of Li(Ni1/3Mn1/3Co1/3)O2 with a nano‐scaled ZnO:Al layer. Issue 1 (6th November 2020) - Wolff, Michael; Lobe, Sandra; Dellen, Christian; Uhlenbruck, Sven; Ribeiro, Caue; Guichard, Xavier H.; Niederberger, Markus; Makvandi, Ardavan; Peterlechner, Martin; Wilde, Gerhard; Fattakhova‐Rohlfing, Dina; Guillon, Olivier
Abstract: In this article, a versatile process based on microwave‐assisted sol–gel synthesis is introduced in order to apply a surface coating on cathode material for lithium‐ion batteries. Here, a nano‐scaled ZnO:Al (AZO) layer is coated homogeneously onto Li(Ni1/3 Mn1/3 Co1/3 )O2 (NMC111) powder at temperatures below 210°C within a few minutes. In contrast to other wet‐chemical coating techniques, the method described here is conducted in a one‐pot reaction and does not require a post‐annealing step at elevated temperatures. Investigations via high resolution transmission electron microscopy (HR‐TEM), scanning transmission electron microscopy (STEM) and inductively‐coupled plasma optical emission spectroscopy (ICP‐OES) promote a thorough understanding of coating microstructure and quality in dependence of reaction temperature, duration and precursor concentration. The AZO protective coating on NMC111 significantly reduces capacity fading during cycling in the voltage range of 3.0‐4.5 V. Furthermore, applying optimal quantities of the coating agent on NMC111 lead to enhanced specific capacities compared to the uncoated material. Abstract : A fast, low‐temperature one‐pot process based on microwave‐assisted sol–gel synthesis is utilized to apply nano‐scaled ZnO:Al coatings on Li(Ni1/3 Mn1/3 Co1/3 )O2 cathode powders. Microstructural characterization reveals a high coating homogeneity and surface coverage. Coated cathode material shows improved capacity retention and higher specific capacities compared to uncoated material.